2009
DOI: 10.1016/j.surg.2009.03.018
|View full text |Cite
|
Sign up to set email alerts
|

Portal annular pancreas, a notable pancreatic malformation: Frequency, morphology, and implications for pancreatic surgery

Abstract: http://dx.doi.org/10.1016/j.surg.2009.03.01

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

1
69
1
2

Year Published

2010
2010
2021
2021

Publication Types

Select...
5
1
1

Relationship

0
7

Authors

Journals

citations
Cited by 64 publications
(73 citation statements)
references
References 4 publications
(4 reference statements)
1
69
1
2
Order By: Relevance
“…A variety of terms have been used to describe this variant, including periportal annular pancreas, 8 circumportal pancreas, 9 and portal annular pancreas. 10 As a result, previous reports have inaccurately tallied the total number of published cases having this variant. 10,11 At least six surgically confirmed cases have been reported in the English literature.…”
Section: Case Reportmentioning
confidence: 99%
See 1 more Smart Citation
“…A variety of terms have been used to describe this variant, including periportal annular pancreas, 8 circumportal pancreas, 9 and portal annular pancreas. 10 As a result, previous reports have inaccurately tallied the total number of published cases having this variant. 10,11 At least six surgically confirmed cases have been reported in the English literature.…”
Section: Case Reportmentioning
confidence: 99%
“…10,11 At least six surgically confirmed cases have been reported in the English literature. [10][11][12][13][14][15] Recent retrospective studies of image records revealed an unexpectedly high incidence of this variant, 10 which highlights poor recognition of this entity. Circumportal pancreas is generally an innocuous and the diagnosis is usually made incidentally.…”
Section: Case Reportmentioning
confidence: 99%
“…Portal annular pancreas (PAP) 13 or the so-called circumportal pancreas 46 /complete pancreatic encasement 7,8 is an asymptomatic, pancreatic anomaly, in which the uncinate process of the pancreas encircles the portal vein and/or its influx, the superior mesenteric and splenic vein, and extends to the dorsal surface of the pancreas body.…”
mentioning
confidence: 99%
“…Two different hypotheses are discussed regarding the development of PAP: either it is a malformation of the portal venous system 8,9 or the pancreas caused by hypertrophy of the ventral 10,11 or dorsal anlagen 3 and subsequent fusion to the left of the mesenteric or portal vein. This anatomic variant is well known from porcine pancreas 12 but described as rare in human, with a prevalence from 1.1% to 3.4% 1,8,13 in computed tomographic (CT) image studies of a healthy population 13 or of patients with hepatoma, adrenal or colon adenoma, uterine carcinoma, or pancreatic cyst, respectively. 1 …”
mentioning
confidence: 99%
See 1 more Smart Citation